2021
DOI: 10.3390/medicina57040359
|View full text |Cite
|
Sign up to set email alerts
|

Primary Mucosal Melanoma Presenting with a Unilateral Nasal Obstruction of the Left Inferior Turbinate

Abstract: We report the case of a primitive nasal melanoma in an 82-year-old patient, showing how this rare malignancy, with non-specific signs and symptoms, can represent a challenging diagnosis for the physician. A 82-year-old Caucasian patient presented for unilateral nasal obstruction and occasional epistaxis. Computerized tomography (CT) and magnetic resonance imaging (MRI) of the facial massif revealed turbinate hypertrophy and a polypoid phlogistic tissue isointense in T1 with an intermediate signal in T2 and Sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…The VDR is expressed in almost all tissues and cells, including the skin. Colston et al [29] provided one of the first reports describing the presence of VDR outside of organs involved in calcium and phosphate homeostasis (intestines, kidneys and bone tissues), showing that the receptor is expressed in skin cell lines and in melanomas (malignant tumors originating from melanocytes) [30] and has anti-cancer properties. Subsequent experiments using human melanoma cell lines confirmed that the VDR is present in melanoma cells, although its expression level was heterogeneous between different cell lines [29].…”
Section: Introductionmentioning
confidence: 99%
“…The VDR is expressed in almost all tissues and cells, including the skin. Colston et al [29] provided one of the first reports describing the presence of VDR outside of organs involved in calcium and phosphate homeostasis (intestines, kidneys and bone tissues), showing that the receptor is expressed in skin cell lines and in melanomas (malignant tumors originating from melanocytes) [30] and has anti-cancer properties. Subsequent experiments using human melanoma cell lines confirmed that the VDR is present in melanoma cells, although its expression level was heterogeneous between different cell lines [29].…”
Section: Introductionmentioning
confidence: 99%
“…This has urged the need for a better biological understanding of the melanoma microenvironment, while also forming the motivation for revolutionizing melanoma treatment in the last decade [ 5 , 6 ]. The gold standard treatment for this condition is surgery, followed by systemic chemo and immunotherapy in more advanced stages [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such investigations could elucidate fluorescence-relevant differences in the subband structures of the melanin absorption spectra. The following examinations using dermatofluoroscopy could contribute to the further qualification of this method for melanoma diagnosis: (i) Inclusion of less frequent melanoma subtypes, e.g., mucosal melanoma [ 36 ], (ii) comparative studies on lentigo (L.) simplex and L. solaris versus L. maligna and L. maligna melanoma, with the aim to support the clinical differentiation of these entities that show overlapping morphology.…”
Section: Discussionmentioning
confidence: 99%